The Aplication of Topical Wharton’s Jelly Mesenchymal Stem Cell Conditioned Medium (Wjmsc-Cm) Inhibit the Increase in Expression of Matrix Metalloproteinase-1 and Increased the Amount of Collagen in the Skin Of Wistar Mice Exposed to Ultraviolet-B Rays - Suarni .; Wimpie Pangkahila; I Gusti Made Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2018)
Introduction: Ultraviolet B exposure is one of the factors causing extrinsic skin aging called photoaging. In this study, stem cell derived media growth factors conditioned from umbilical cord was used. The purpose of this study is to prove that topical administration of Wharton’s Mesenchymal Stem Cell Conditioned Medium Jelly (WJMSC-CM) could inhibit the increase in expression of matrix metalloproteinase-1 and increases the amount of collagen in the skin of wistar rats exposed to ultraviolet-B light. Methods: An animal experimental with Post-test Only control group design study was conducted to evaluate the aforementioned hypothesis. The number of samples used in this study was 36 wistar rats, aged 3-4 months and were divided into 2 groups: the control group consisted of 18 rats and were given placebo glycerin gel and exposed to UV B rays, while the treatment group was given WJMSC-CM and exposed to UV B rays. All treatments were given UV B rays with a total irradiation dose of 840mj / cm2 for 4 weeks. The study was carried out at the Laboratory Animal Unit Unit of Pharmacology, Faculty of Medicine, Udayana University, Denpasar. Results: By using the Shapiro Wilk test for numerical data with normal distribution, Levene’s Test showed that the distribution of data and variants are homogeneous groups for both groups. The results of the comparative analysis of the two groups using independent t-test showed significant differences between the two groups on MMP-1 expression and the amount of collagen (p <0.05). Conclusion: The conclusion of this study is the administration of WJMSC-CM topically inhibits the increase in MMP-1 expression and increases the amount of collagen in wistar rats exposed to UV B light.